Combining Whole-Brain Radiotherapy with Gefitinib/Erlotinib for Brain Metastases from Non-Small-Cell Lung Cancer: A Meta-Analysis. (24th February 2016) - Zheng, Mao-hua; Sun, Hong-tao; Xu, Ji-guang; Yang, Gang; Huo, Lei-ming; Zhang, Pan; Tian, Jin-hui; Yang, Ke-hu
Abstract : Background . To comprehensively assess the efficacy and safety of whole-brain radiotherapy (WBRT) combined with gefitinib/erlotinib for treatment of brain metastases (BM) from non-small-cell lung cancer (NSCLC). Methods . Databases including PubMed, EMBASE.com, Web of Science, and Cochrane Library were searched from inception to April 12, 2015. Studies on randomized controlled trials (RCTs) and case-control trials comparing WBRT combined with gefitinib/erlotinib versus WBRT alone for BM from NSCLC were included. Literature selection, data extraction, and quality assessment were performed independently by two trained reviewers. RevMan 5.3 software was used to analyze data. Results . A total of 7 trials involving 622 patients were included. Compared with WBRT alone or WBRT plus chemotherapy, WBRT plus gefitinib/erlotinib could significantly improve response rate (OR = 2.16, 95% CI: 1.35–3.47; P = 0.001 ), remission rate of central nervous system (OR = 6.06, 95% CI: 2.57–14.29; P < 0.0001 ), disease control rate (OR = 3.34, 95% CI: 1.84–6.07; P < 0.0001 ), overall survival (HR = 0.72, 95% CI: 0.58–0.89; P = 0.002 ), and 1-year survival rate (OR = 2.43, 95% CI: 1.51–3.91; P = 0.0002 ). In adverse events (III-IV), statistically significant differences were not found, except for rash (OR = 7.96, 95% CI: 2.02–31.34; P = 0.003 ) and myelosuppression (OR = 0.19, 95% CI: 0.07–0.51; P = 0.0010 ). Conclusions . WBRT plus gefitinib/erlotinib was superior to WBRT alone and well tolerated in patients with BM from NSCLC.